International perspectives on socio-economic development in the era of globalization - Sen, Sourabh Bhattacharya, Anshuman Sen, Ruchi; Sen, Saurabh (USA IGI Global, 2016)
"This book seeks to examine the existing variability of development in the global marketplace and to identify the catalysts responsible for this disparity of success, analyzing the economic frontiers, social norms, and infrastructural capabilities that factor into the socio-economic growth of the developing and under-developed world"--
Analyzing the roles of human capital and competency in global business -- An empirical analysis of 7ps' elements on tourists satisfaction: a case from Bishnupur -- Assets management of the Indian pharma sector in the changing socio-cultural and business environment of post-liberalization era : a comparative study on select multinational and domestic companies -- Can codes of conduct work? : evaluating the effectiveness of privatised corporate governance -- Financial inclusion in India : an assessment -- Perception of residents on ecotourism in Uttarakhand -- Women's empowerment and socio-economic development in MENA region : adaptation to trade policies and access to market for promoting entrepreneurship -- A measurement-based e-government portals : maturity model -- Challenges of disinvestment in public sector banks -- Basel III a step ahead in banking risk management -- Green marketing in India : a theoretical perspective -- Green manufacturing : the need of the hour for developing nations : a case study -- Online banking -- Human resource development in globalized era -- Corporate ethics and social responsibility -- Self help groups- bank linkage model in India -- Computational investing.
Keywords: Economic development; Human capital; Social change; Globalization